HYPERTROPHIC CARDIOMYOPATHY IN ATHLETES - A LITERATURE REVIEW - Wiktoria Smyła-Gruca,; Marcin Gruca,; Katarzyna Kost,; Sylwia Boczek,; Mikołaj Herba, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Hypertrophic cardiomyopathy (HCM) is one of the most common hereditary heart muscle disorders. It is characterised by unexplained left ventricular hypertrophy (LVH). In competitive sports, HCM can be particularly dangerous. It is a well-recognised leading cause of sudden cardiac death (SCD) among young athletes.Aim: This study aimed to provide a comprehensive review of the current understanding of HCM within athletic populations, with a focus on the differences in pathophysiology compared to normal physiological adaptation.Material and methods: Between April and July 2025, we searched the PubMed, Google Scholar, and PMC databases. We used both Medical Subject Headings (MeSH) and keywords in the free text. The search was limited to studies on humans. Due to the heterogeneity of the materials used, no statistical analyses or quantitative pooling were performed. The narrative was based on PRISMA principles.Research results: HCM is a genetic disorder caused by mutations in sarcomere-affecting genes. These abnormalities result in abnormal energy metabolism, disturbances in calcium homeostasis and oxidative stress. This generates an energy deficit, which is exacerbated further during competitive sports. This mechanism can lead to life-threatening complications. Distinguishing between the heart's physiological adaptation to intense physical exertion and HCM requires an assessment of ventricular geometry, diastolic and systolic performance, coronary perfusion and the body's response to exercise testing.Conclusion: HCM presents many challenges to sports medicine and diagnosis requires advanced tests. Thanks to extensive research on HCM, the range of therapeutic options in both pharmacotherapy and surgical treatment is constantly expanding.